Slum Upgrading Spatial Model Based on Level of Vulnerability to Climate Change in Coastal Area of Semarang City - Khristiana Dwi Astuti; P Pangi; Reny Yesiana; Intan Muning Harjanti (Geoplanning: Journal of Geomatics and Planning, 2021)
Slum settlement is one of the significant global problems which requires special concern in the discussion agenda of Sustainable Development Goals (SDGs) of 2016-2030. The Sustainable Development Summit held in New York in September 2015 formulated that one of SDGs goals is to build inclusive, safe, resilient, and sustainable cities and settlements. In Indonesia, the achievement of this goal is stated in National Medium-Term Development Plan 2015-2019, i.e. creating 0% urban slum settlement which is supported by policies expected to accommodate the achievement of national development targets. Semarang Mayor Decree No. 050/801/2014 concerning the Determination of the Location of Housing Environment and Slum Settlements in Semarang City has been issued as the basis to identify slum settlements scattered throughout Semarang city, in terms of location, physical condition, and social conditions. This study was conducted by case studies on slum settlements in Trimulyo Village and Mangkang Wetan Village, Semarang city, Central Java Province, Indonesia, to formulate a slum upgrading model based on the resilience level of coastal communities towards climate change. The analysis included identifying the characteristics of slum settlements, scoring analysis to determine the resilience level possessed by coastal communities, and analysis of pentagon assets used to formulate slum upgrading models. The results of the study showed that these two research areas had a moderate level of vulnerability, with several different characteristics of asset ownership, particularly those related to human and social assets. Increasing the quality of human resources and social relations in the community was more intensified in the environment and community in Trimulyo, while improving the physical quality of the environment through housing improvements was carried out in Mangkang Wetan.